Digitalisasi dan Frictional Unemployment: Analisis Dampak dan Efisiensi Pasar Tenaga Kerja - M.Firmansyah; Dadang Wibowo (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2026)
The digital era has brought significant transformations to various aspects of life, including the labor market. These changes have impacted the dynamics of frictional unemployment, which is temporary unemployment that arises due to the time lag between leaving a current job and finding a new one. On the one hand, digitalization accelerates the matching of workers with companies through digital platforms and modern recruitment technologies. However, on the other hand, digitalization also creates skills mismatches and increases the risk of job insecurity, especially in the digital economy and gig economy sectors. This study aims to analyze how digitalization affects frictional unemployment, both positively and negatively, and to provide strategic recommendations to mitigate its negative impacts. Using a literature review approach and descriptive analysis, the results show that digitalization can reduce frictional unemployment if the workforce has adequate digital literacy. Conversely, for those who are less skilled, digitalization actually prolongs unemployment